Cultivating Teacher Resilience 2020
DOI: 10.1007/978-981-15-5963-1_14
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Teacher Wellbeing Through Job Demands-Resources Theory

Abstract: Job demands-resources (JD-R) theory has emerged as one of the most influential conceptual frameworks for interpreting and explaining factors affecting employees' wellbeing in the workplace. The present chapter provides a broad overview of JD-R theory, and discusses how the theory can be harnessed to further understand the factors influencing teachers' wellbeing. The chapter also reviews prior research employing JD-R theory in teaching populations, and explores the job demands (e.g., workload, disciplinary issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(115 citation statements)
references
References 44 publications
7
64
0
14
Order By: Relevance
“…Teachers’ self-efficacy, regarded as the correct perception of one’s own abilities and an interest in developing students’ competencies, is known to positively influence students’ performance, involvement, wellbeing, attitude towards school, and academic success [ 34 ]. Concurrently, teachers’ self-efficacy has been proved to be a predictor of higher engagement and lower burnout [ 35 ], which advocates the complementarity of the factors investigated in this study. A study revealed that an 8-month computer training program for teachers, in terms of its integration into education, significantly reduced teacher computer anxiety [ 36 ].…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 87%
“…Teachers’ self-efficacy, regarded as the correct perception of one’s own abilities and an interest in developing students’ competencies, is known to positively influence students’ performance, involvement, wellbeing, attitude towards school, and academic success [ 34 ]. Concurrently, teachers’ self-efficacy has been proved to be a predictor of higher engagement and lower burnout [ 35 ], which advocates the complementarity of the factors investigated in this study. A study revealed that an 8-month computer training program for teachers, in terms of its integration into education, significantly reduced teacher computer anxiety [ 36 ].…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 87%
“…As stated above, work engagement increasingly represents a critical job-related motivational construct as it relates to several relevant outcomes within educational settings (Taris et al, 2017;Granziera et al, 2021). For example, work engagement is positively associated with teachers' job satisfaction, which in turn impacts students' development and academic achievement (Perera et al, 2018).…”
Section: Teachers' Work Engagement: Personal and Work-related Correlatesmentioning
confidence: 99%
“…Current knowledge suggest that levels of work engagement are closely related to teachers' attitudes toward their work and life, which has key implications in educational settings (Perera et al, 2018;Granziera et al, 2021). Although work engagement might be an important factor linked to teachers' personal and work-related well-being (Schaufeli and Taris, 2014), it is shown that low work engagement does not necessarily lead to low levels of work-related indicators (Parker and Griffin, 2011).…”
Section: Teachers' Work Engagement: Personal and Work-related Correlatesmentioning
confidence: 99%
See 2 more Smart Citations